Analytical assessment of a novel hybrid solar tubular receiver and combustor. (15th January 2016) - Lim, Jin Han; Nathan, Graham J.; Hu, Eric; Dally, Bassam B.
Highlights: We present a novel hybrid between a solar cavity receiver and a combustor. The economic benefit of this integration is confirmed. The combustor can achieve the same efficiency as a conventional boiler. Abstract: This paper presents a novel hybrid between a tubular solar receiver and a combustor, called the Hybrid Solar Receiver Combustor (HSRC), and reports on the development and application of an analytical model to describe its performance. The analytical model accounts for the variability of the solar resource with a pseudo steady state balance of the mass and energy flow, which calculates the heat transfer throughout the device. A systematic investigation of the influence of variation in all controlling parameters on performance and weight is undertaken. The results provide new understanding of the performance of the device relative to the solar-only and combustion-only counterparts, and further justification for its ongoing development.